1984
DOI: 10.1021/jo00200a034
|View full text |Cite
|
Sign up to set email alerts
|

Solvent ionizing power - comparisons of solvolyses of 1-adamantyl chlorides, bromides, iodides, and tosylates in protic solvents

Abstract: Solvolytic rate constants for 1-adamantyl iodide (1-AdI) in binary aqueous mixtures of ethanol, methanol, acetone, trifluoroethanol, and hexafluoroisopropyl alcohol and in acetic and formic acids are reported. Additional kinetic data for solvolyses of 1-adamantyl halides in 97% w/w hexafluoroisopropyl alcohol/water were obtained by using a microconductivity cell (volume, ca. 0.4 mL). Kinetic data for iodine-catalyzed solvolyses of 1-AdI in methanol/water mixtures are also reported. A scale of solvent ionizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
2

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
1
32
0
2
Order By: Relevance
“…The values (Table 1) for 97% HFIP are in very good agreement with earlier determinations [14,15]. The specific rates are the averages from at least four independent kinetic runs.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The values (Table 1) for 97% HFIP are in very good agreement with earlier determinations [14,15]. The specific rates are the averages from at least four independent kinetic runs.…”
Section: Resultssupporting
confidence: 88%
“…Variations in Y x values for different leaving groups will have components both from differences in interactions in the solvent under consideration and from differences in interactions in the 80% ethanol. However, the observation that the 1-AdI/1-AdBr specific rate ratio varies only from 2.3 in 90% EtOH to 1.9 in 60% EtOH [14] suggests that interactions in ethanol-rich ethanol-water mixtures are similar for different halides. In contrast, appreciably larger variation (0.46 to 1.14) is observed over the similar concentration range of 97% HFIP to 70% HFIP, consistent with the dominant influence of differences in the interactions of the various 1-adamantyl halides with a more electrophilic fluoroalcohol-rich solvent.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The reaction rate decreases, and with adamantyl substrates this effect is stronger than with tert-butyl substrates. Since only the relative effect of the solvent nucleophilicity was determined, it was erroneously concluded that a solvent renders nucleophilic assistance in the heterolysis of tert-butyl substrates [4,7,8].The negative effect of the nucleophilic solvation is observed only in the heterolysis of tertiary substrates; it is indicative of the nonequilibrium solvation of the transition state when the solvation shells of the ground and excited states have different structures. This effect is usually pronounced in protic solvents, which is apparently associated with hydrogen bonding between molecules solvating nucleophilically and electrophilically pair A.…”
mentioning
confidence: 99%